2022
DOI: 10.1186/s13023-022-02246-4
|View full text |Cite
|
Sign up to set email alerts
|

Social and clinical impact of COVID-19 on patients with fibrodysplasia ossificans progressiva

Abstract: Background COVID-19, caused by the SARS-CoV-2 virus, is a severe inflammatory condition. Patients with pre-existing conditions including diabetes, hypertension, and cardiovascular disease are at particularly high risk of complications. Fibrodysplasia ossificans progressiva (FOP) is an ultra-rare and debilitating genetic disorder that is characterized by a pro-inflammatory state, which leads to progressive heterotopic ossification and complications after trauma, including intramuscular vaccinati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Several studies have documented a strong correlation between coronavirus disease 2019 (COVID-19) and the development of ectopic ossification[ 14 , 15 ]. Meanwhile, MO cases have occurred among patients receiving the COVID-19 vaccine[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented a strong correlation between coronavirus disease 2019 (COVID-19) and the development of ectopic ossification[ 14 , 15 ]. Meanwhile, MO cases have occurred among patients receiving the COVID-19 vaccine[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the total of 22 months of observation, we found that vaccination of patients with FOP with the COVID-19 vaccines could be well tolerated, using the guidelines published in our original manuscript [ 1 ] and on the ICCFOP.org website [ 2 ]. ICC FOP guidelines for COVID-19 Vaccine Injections included taking the vaccine through its intended route, taking the vaccine at a location that is already fused, avoiding vaccination sites exposed to pressure (such as the buttocks), being flare-free for at least 2 weeks prior, using the smallest diameter needle available, and taking ibuprofen or acetaminophen before the vaccination and for 48 h after the injection.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the propensity for post-traumatic flare activity and progressive HO formation characteristic of FOP, we had originally hypothesized that COVID-19 infection and vaccination may have disproportionately negative impacts on people with FOP. Our observations on a small cohort suggest that patients with FOP have similar risks as the general population to COVID-19 infection, and that patients with FOP may be able to tolerate COVID-19 vaccination when treated following a consensus protocol to mitigate flare risk [ 1 ]. Because other vaccinations and viral infections are known [ 4 7 ] to be associated with HO formation in patients with FOP, this information should be used to guide individual discussions about risks and benefits for vaccination within the FOP community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation